DaHuangWan targets EGF signaling to inhibit the proliferation of hepatoma cells - Si, Ha; Genna, Ba; Zhuang, Xiangjin; Wang, Jing; Burenbatu, B.; Feng, Qiyu; Wang, Hongyang (PloS one, 2020)
DaHuangWan (DHW) is a traditional herbal medicine used by Mongolian to treat liver cancer for many years. Clinical application of the drug has been shown to help control tumor progression, prolong survival and improve quality of life. However, the underlying mechanisms and side effects of this drug remain unclear, which greatly limits the clinical application and further optimization of DHW. In this study, we found that DHW inhibits the proliferation of hepatoma cells by modulating the epithelial growth factor (EGF) signaling pathway. Berberine and Costunolide are the main active ingredients in DHW. Interestingly, the combination of Berberine and Costunolide has a dramatic synergistic effect on inhibiting the proliferation of hepatoma cells. Neither Berberine nor Costunolide directly block EGFR phosphorylation. Berberine promotes endocytosis of activated EGFR, while as Costunolide increases ubiquitination of EGFR and reduces EGFR recycling to cell membrane distribution, thereby inhibiting EGF signaling. Berberine and Costunolide target two different steps in regulating the EGF signaling, which explains the synergistic anti-cancer effect of DHW. Since Berberine and Costunolide do not directly target EGFR phosphorylation, DHW could be a supplementary medicine to tyrosine kinase inhibitors in cancer therapy.